Arthroscopic rotator cuff repair in elite rugby players - Tambe, Amol (Medknow Publications, 2009)
BACKGROUND: Rugby is an increasingly popular collision sport. A wide spectrum of injuries can be sustained during training and match play. Rotator cuff injury is uncommon in contact sports and there is little published literature on the treatment of rotator cuff tears in rugby players. AIMS: We therefore reviewed the results and functional outcomes of arthroscopic rotator cuff repair in elite rugby players. MATERIALS AND METHODS: Eleven professional rugby players underwent arthroscopic rotator cuff repair at our hospital over a 2-year period. We collected data on these patients from the operative records. The patients were recalled for outcome scoring and ultrasound scans. RESULTS: There were seven rugby league players and four rugby union players, including six internationals. Their mean age was 25.7 years. All had had a traumatic episode during match play and could not return to the game after the injury. The mean time to surgery was 5 weeks. The mean width of the cuff tear was 1.8 cm. All were full- thickness cuff tears. Associated injuries included two Bankart lesions, one bony Bankart lesion, one posterior labral tear, and two 360° labral tears. The biceps was involved in three cases. Two were debrided and a tenodesis was performed in one. Repair was with suture anchors. Following surgery, all patients underwent a supervised accelerated rehabilitation programme. The final follow-up was at 18 months (range: 6–31 months) post surgery. The Constant scores improved from 44 preoperatively to 99 at the last follow-up. The mean score at 3 months was 95. The Oxford shoulder score improved from 34 to 12, with the mean third month score being 18. The mean time taken to return to full match play at the preinjury level was 4.8 months. There were no complications in any of the patients and postoperative scans in nine patients confirmed that the repairs had healed. CONCLUSION: We conclude that full-thickness rotator cuff tears in the contact athlete can be addressed successfully by arthroscopic repair, with a rapid return to preinjury status.